Neolithic Culture: the issues of interpretation - Vladimir V. Stavitsky (Археология евразийских степей)
In Soviet science, the prevailing viewpoint was that the Neolithic culture corresponded to a group of related tribes. A.A. Formozov and M.V. Voyevodsky also distinguished larger communities: cultural areas, zones, provinces. The study of Australian aborigines has shown that they had no division into tribes. The basis of their social structure was local groups (communities), and all larger associations were amorphous and unstable. Each community was at the Centre of its social ties, that led to primeval cultural continuity, which, in the absence of natural and geographical obstacles, had no clearly defined boundaries. Ethnic kinship was not a decisive factor in the process of formation of similar features of material culture. The decisive significance was the belonging to a single economic and cultural type, which facilitated contacts between Neolithic communities. Three main cultural and economic types can be distinguished for the population of the East European Plain: 1) hunters of steppes and forest steppes on large gregarious herbivores, 2) forest hunters and fishermen of the temperate zone, 3) semi-sedentary fishermen of forest rivers of the temperate zone. The ethnographic analogue of archaeological culture is a historical and cultural area, which often has an ethnically heterogeneous structure, and its components are not necessarily connected by common origin. In the Neolithic, the boundaries of such areas coincide with large river basins and natural landscape zones. The archaeological culture of the Neolithic represents a peculiar clot of cultural and primeval continuity.